The association between body composition, quality of life (QoL), overall survival (OS) and decision to treat (DTT) in patients with metastatic non–small cell lung cancer (mNSCLC). Issue 28 (1st October 2022) - Lee, Hyejung; Haaland, Ben; Akerley, Wallace L.; Coletta, Adriana M; Yap, Jeffrey T.; Puri, Sonam; Kerrigan, Kathleen Claire
Abstract : 377 Background: Among patients diagnosed with mNSCLC, significant declines in fat and muscle mass are common, yet there is a paucity of data related to body composition, QoL, TD, and survival. Accordingly, we evaluated the relationship between body composition via routine CT scans, patient-reported outcomes (PROs), and overall survival (OS) among a convenience sample of mNSCLC patients. Methods: Data from 80 mNSCLC patients with initial CT scans and NCI PROMIS questionnaires within the first three months of diagnosis were analyzed. Body composition from CT scans (sliceOmatic software) extracted Skeletal muscle (SM), intermuscular adipose tissue (IAT), visceral VAT, and subcutaneous (SAT) in area (cm2) and a discovery set was expressed as HU. PROMIS PROs (pain, fatigue, anxiety, depression, and physical function) were collected in clinic using an iPad as an institutional quality initiative. Results: Median time to OS was 16 months. When stratified by sex, females had longer median survival time (female 25 months, male 14 months). When all body composition variables were considered together, greater amounts of skeletal muscle were linked with a 63% reduction in mortality risk 0.37 (95% CI 0.16, 0.87) in the adjusted model. Per one-unit increase in VAT (area cm2) was linked with a 0.04 unit decrease in pain (95% CI -0.08, -0.01). Associations between HU and clinical were also observed. Greater amount of VAT (mean HU) was linked with 2.57(95% CI 1.10, 6.01) times the odds of death in the crude model. Also, in crude model, one unit of increase in skeletal muscle (mean HU) was associated with 0.3 (95% CI 0.03, 0.57) unit increase in physical functionality, and -0.34(95% CI -0.63, -0.05)) unit decrease in fatigue. Conclusions: Body composition data can be collected from retrospective scans and appears to be prognostic of OS, PRO and TD.